2015
DOI: 10.1177/0268355515573686
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in vascular and circulating blood cells following exposure to detergent sclerosants

Abstract: Detergent sclerosants are biologically active at sublytic concentrations. The observed morphological changes are consistent with cell activation, apoptosis, and oncosis. The cellular response is concentration dependent, cell-specific, and sclerosant specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…1 In a recent study, morphological evidence of sclerosant-induced nonlytic forms of cell death in vascular and circulating blood cells exposed to detergent sclerosants was observed. 2 The cytoplasmic and nuclear changes were consistent with typical morphological changes observed in cells undergoing apoptosis and oncosis. Prior to the present study there has been no attempt to investigate a possible apoptotic effect of sclerosant on cells exposed to these agents during sclerotherapy.…”
Section: Introductionsupporting
confidence: 76%
“…1 In a recent study, morphological evidence of sclerosant-induced nonlytic forms of cell death in vascular and circulating blood cells exposed to detergent sclerosants was observed. 2 The cytoplasmic and nuclear changes were consistent with typical morphological changes observed in cells undergoing apoptosis and oncosis. Prior to the present study there has been no attempt to investigate a possible apoptotic effect of sclerosant on cells exposed to these agents during sclerotherapy.…”
Section: Introductionsupporting
confidence: 76%
“…In a recent study, we observed morphological evidence of apoptosis and oncosis on endothelial cells after exposure to sublytic concentrations of detergent sclerosants [6]. Further studies demonstrated that both sclerosants were capable of inducing apoptosis and oncosis on leukocytes [7].…”
Section: Introductionmentioning
confidence: 81%
“…Porimin mediates oncosis-like cell death and is characterised by cell swelling, organelle swelling, vacuolisation and increased membrane permeability [25]. We previously demonstrated that detergent sclerosants induce morphological changes consistent with oncosis on different cells including HUVECs [6]. The mechanism of cellular death through the oncotic pathway implies an increase in membrane permeability caused by the failure of the ionic pumps of the plasma membrane and is associated with an increase in cytosolic calcium and a rearrangement of cytoskeletal proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Los esclerosantes osmóticos como la solución salina al 30% o la solución dextro/ sal hipertónica, que producen lisis de las células epiteliales por deshidratación (10)(11)(12). Los esclerosantes químicos irritantes como alcohol absoluto (etanol al 98%), el glicerol cromado y la iodina poliodinatada, que producen destrucción celular y necrosis por citotoxicidad; y los esclerosantes detergentes como el polidocanol (tetradecilsulfato de sodio al 3%), etanolamina y el clorhidrato de lapidium que interactúan con los lípidos de la membrana de las células epiteliales, produciendo la lisis celular por disminución de la tensión superficial resultando en esclerosis, retracción tisular y obliteración de los quistes y vasos sanguíneos (10)(11)(12).…”
Section: Existen 3 Grupos De Sustancias Esclerosantesunclassified
“…La esclerosis se caracteriza por la destrucción celular epitelial con apoptosis, inflamación estéril, fibrosis irreversible y disminución de la masa tisular por retracción con subsecuente obliteración de la luz de los quistes y/o vasos sanguíneos y la formación de trombo intravascular, denominado esclerotrombo, que sella la circulación (10)(11)(12).…”
unclassified